Argyrochosma nivea (Poir.) Windham (Pteridaceae): An ethnobotanical, ethnopharmacological and phytochemical revision - Minchán-Herrera, Patricia Ivonne; Saldaña-Bobadilla, Vanessa; Perez-Chauca, Enma; Ramirez, J-Kenedy (Ethnobotany Research and Applications, 2020)
Background: Argyrochosma nivea (Poir.) Windham from the Pteridaceae family E.D.M. Kirchn, grows wild in the tropical Andes, humid and mountainous landscapes. Traditionally, it is used to treat various conditions; However, the lack of a system or means of source of information with scientific rigor that corroborates the pharmacological effects conferred on the plant, causes potential problems that would affect the population, either due to a phytotherapeutic failure or due to the appearance of unwanted effects. Therefore, this review aims to gather and analyze the information available on Argyrochosma nivea on ethnobotanical, ethnopharmacological and phytochemical aspects. Methods: The information collection on Argyrochosma nivea was carried out using the Scopus, ScienceDirect, PubMed databases and the CONCYTEC virtual library; in addition, the Google-Academic search engine was used. The search terms were “Argyrochosma nivea”, “Notholaena nivea” or “cuti cuti”. Results: The use of the plant in traditional medicine is varied; for example, for the treatment of diabetes, to treat infectious conditions, as an anti-inflammatory, analgesic and even for a toxic (abortifacient) effect. Preliminary studies are evidenced to evaluate the hypoglycemic, antibacterial and antioxidant effects; in addition to the identification of 10 compounds in the plant. Conclusions: The available information on the plant was gathered and analyzed, structuring them in ethnobotanical, ethnopharmacological and phytochemical aspects. In addition, scientific gaps that affect the proper use of the plant were identified. Keywords: Notholaena nivea; Cuti-Cuti; Pteridaceae; antidiabetic; Phytotherapy; traditional medicine.